KURIKULUM DALAM TINJAUAN FILSAFAT REKONSTRUKSIANISME - Rohmat Rohmat (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2019)
The curriculum development model in the philosophy of reconstructionism review is a model that is usually used in many curriculum development processes. In this model the curriculum mostly takes the first position, namely as a plan and activity. The ideas developed in the initial steps focus more on what qualities must be possessed through learning about scientific disciplines, technology, religion, art, and so on. The nature of the objectives of the education curriculum according to reconstructionism are: (1) changing society in accordance with economic needs, (2) changing society in accordance with certain values. The curriculum is a science design that will be achieved through education.